Analisis Dampak Aktivitas Produksi Migas Terhadap Kualitas Air Bersih yang Digunakan Masyarakat Pandan Sari - Sambata, Yunsel Ade Noel; Hidayat, Irfan; Prasetya, Kiftian Hady (Department of Industrial Engineering, Faculty of Industrial Technology, Universitas Balikpapan, 2026)
The availability of clean water is a basic human need that must be maintained, especially for communities living around oil and gas industrial areas. Oil and gas production activities, which involve chemical processes, oil processing, and industrial waste disposal, have the potential to degrade environmental quality, particularly the clean water used by residents on a daily basis. This study aims to analyze the impact of oil and gas refinery activities on clean water conditions in the surrounding area from a physical, chemical, and social perspective. The method used is a qualitative descriptive approach through direct interviews, questionnaires, field observations, and literature studies related to industrial waste management. The results show a decline in water quality in several locations adjacent to the refinery, characterized by discoloration, unpleasant odors, and health complaints from local residents. Furthermore, new economic burdens arise due to the need to purchase clean water because well water is no longer suitable for consumption. These findings emphasize the importance of stricter environmental monitoring, responsible waste management, and the provision of alternative clean water sources for affected communities. Collaboration between companies, the government, and the community is a key factor in maintaining the sustainability of water resources in oil and gas industrial areas.